Optimization of Human Resource Management in Islamic Boarding Schools - Susanto, Tri Joko; Baidi, Baidi; Imam Sukardi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2025)
This study aims to analyze the human resource management system (HR) at the Daar El Qolam 3 Islamic Boarding School in Tangerang as a model of modern Islamic education management that integrates spiritual values with the principles of professionalism. This research focuses on three main aspects: (1) the management of teaching and education personnel, (2) the management of students through an integrated education and parenting system, and (3) the management and empowerment of alumni as part of the sustainability strategy of the Islamic boarding school. This study uses a qualitative descriptive approach using a case study method. Data were collected through observation, in-depth interviews, and documentation studies of internal documents of the pesantren, and analyzed using the Miles and Huberman interactive model. The findings show that HR management at Daar El Qolam 3 operates in a systematic and value-based manner. Faculty management is carried out through selective recruitment, training, competency certification, and performance evaluation based on moral and spiritual values. Student management is carried out in an integrative manner, combining academic education and character development through the MUMTAZA student organization as well as leadership and social programs. Alumni management is carried out through IKADEQ, an alumni organization that functions as a platform for collaboration and strengthening academic, social, and international networks with foreign universities. This study concludes that the success of HR management in Daar El Qolam 3 is supported by the internalization of Islamic values such as sincerity, simplicity, brotherhood, and responsibility into the modern managerial system. This model increases the attractiveness and competitiveness of Islamic boarding schools in the global era and serves as a reference for other Islamic educational institutions in building professional, spiritual, and sustainable human resource management.